A STUDY OF MARKETING STRATEGIES ADOPTED BY ANKUR SEEDS PVT LTD IN YAVATMAL DISTRICT - Amardeep Bajpai (International Journal of Research Science and Management, 2016)
A research driven organization, Ankur seeds is a pioneer &dynamic agricultural biotech company delivering high quality seeds for the Indian seeds market. Ankur is working on cotton, rice, okra, tomato, chili, brinjal, gourds, wheat, pigeon pea, beans and sunflower.